2015
DOI: 10.2344/0003-3006-62.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Needle Design on Pain From Dental Local Anesthetic Injections

Abstract: The purpose of this randomized, double-blind clinical study was to evaluate the effectiveness of a larger-bore compared with a standard-bore dental local anesthetic needle of the same gauge in reducing pain during inferior alveolar (IA) and long buccal (LB) nerve block injections. Twenty active duty military or Department of Defense beneficiaries undergoing dental treatment were anesthetized using a splitmouth design with 4 anesthetic dental injections. Both sides of the mouth received IA nerve block and LB ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
1
17
0
1
Order By: Relevance
“…reported scores of 38.9‐38.7 mm/100 mm for larger and standard‐bore needles, respectively, when using traditional syringes and injection techniques for the inferior alveolar nerve block . In the same study, VAS scores of approximately 35 mm/100 mm were found for a traditional injection technique during anesthesia of the long buccal nerve . In our study, 86% of patients declared less discomfort than that perceived during their last traditional procedure for pain control.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…reported scores of 38.9‐38.7 mm/100 mm for larger and standard‐bore needles, respectively, when using traditional syringes and injection techniques for the inferior alveolar nerve block . In the same study, VAS scores of approximately 35 mm/100 mm were found for a traditional injection technique during anesthesia of the long buccal nerve . In our study, 86% of patients declared less discomfort than that perceived during their last traditional procedure for pain control.…”
Section: Discussionsupporting
confidence: 66%
“…For a comparison of values, using a 100‐mm VAS scale, McPherson et al. reported scores of 38.9‐38.7 mm/100 mm for larger and standard‐bore needles, respectively, when using traditional syringes and injection techniques for the inferior alveolar nerve block . In the same study, VAS scores of approximately 35 mm/100 mm were found for a traditional injection technique during anesthesia of the long buccal nerve .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Injection site preparation methods include application of topical anesthesia, precooling the injection site [ 16 17 18 19 ], and vibratory (physical) stimulation of the injection site [ 20 21 ]. Psychological methods include distraction [ 22 23 24 25 26 27 28 ], technical changes, such as changing the needle diameter [ 29 30 ], and warming and buffering the local anesthesia solution. These methods reduce the discomfort associated with intraoral local anesthesia administration [ 31 32 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological methods include distraction [22][23][24][25][26][27][28], technical changes, such as changing the needle diameter [29,30], and warming and buffering the local anesthesia solution. These methods reduce the discomfort associated with intraoral local anesthesia administration [31][32][33].…”
Section: Not Evaluatedmentioning
confidence: 99%